MAKNA RIMPU SEBAGAI MEDIA KOMUNIKASI NONVERBAL BAGI PEREMPUAN BIMA - Rahmi Rahmi (Universitas Mbojo Bima, 2016)
This research is motivated rimpu culture which is one of the cultural community in general Bima, in which women wear to cover nakedness rimpu as Islam teaches that each of the womenwho have had to cover the nakedness â€œAqil balikâ€ in front of people who are not strange. In asociety Simpasai sarimpu realized by using a form of obedience to Allah SWT.Rimpu culture began to be known since the advent of Islam in Bima brought by religious leaders from Gowa Makassar. Although the community it self knows no cultural Gowa rimpu sorimpu culture is the result of womenâ€™s culture, especially in Simpasai Bima. Rimpu is wearinggloves to wrap the head in which the wearerâ€™s face visible only by using gloves.Rimpu is a type of clothing womenâ€™s clothing Simpasi in which a part of nonverbalcommunication. Rimpu in the context of nonverbal communication has its own meanings. Asindividual expression which through this rimpu communicate about the values that are believedto users. Is a personal identity or a particular social group. In addition, rimpu reflect the statusof a woman in a community, he will be judged as a good woman and family well too if you wearrimpu. Rimpu also communicate the economic status of the wearer this can be seen from thetype of glove wearing. Women who wear rimpu will also be assessed as a woman who religionbecause obedient to God Almighty to cover nakedness.